Skill acquisition and work in micro-enterprises : evidence from Lomé, Togo - Fluitman, Fred [Verfasser]; Oudin, Xavier [Verfasser] (International Labour Office, 1991)
"This paper presents the results of a survey carried out in 1989 in Lomé, Togo, on skill acquisition and work in micro-enterprises. The survey is one of several undertaken jointly by the World Bank, the ILO and the Development Centre of the OECD in Sub-Saharan Africa to trace and explain the careers of micro-entrepreneurs in selected trades and to investigate their role as trainers of apprentices. Interest in the subject is associated with problems facing a large majority of labour market entrants for whom there is no chance ever of wage-employment in the modern sector of economy. It is a major challenge to prevent their marginalisation and indeed to enhance productivity and output as well as the working conditions of people who end up in the formal sector. The study is intended to assist governments and development agencies in designing and implementing pertinent education and training policies." (Excerpt, BIBB-Doku)
Keywords: S 3.2.1 KMU, Klein- und Mittlere Unternehmen; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; Berufsausbildung; Arbeitsmarkt; Klein- und Mittelbetrieb; Arbeitnehmer; Frauen